Notes on the Current Status of Wisconsin Unionidae - Wills Flowers (Hello World!, 1975)
In recent years, there has been great concern about the status of American mussels, the Unionidae. Much of this concern arises from changes in river systems where Ortmann and other early workers reported abundant naiad populations. Recent surveys of these same streams have often shown marked reduction in species diversity (Stansbery, 1964, 1972; Starrett, 1971; Isom and Yokley, 1967, 1968; van der Schalie, 1973. One of the most thorough surveys of the naiad fauna within the Mississippi drainage is the work of Baker (1928) on Wiscons in Unionidae. Since 1928, only surveys by Dawley (1947) of the lower St.Croix and Mississippi Rivers have dealt with the Wisconsin fauna.